2018
DOI: 10.1136/heartjnl-2018-313492
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose combination antihypertensives and risk of medication errors

Abstract: ObjectiveWhile fixed-dose combinations (FDC) can improve adherence, they may add complexity to the prescribing/dispensing process, potentially increasing risk of medication errors. This study aimed to determine if prescriptions for antihypertensive FDCs increase the risk of therapeutic duplication and drug–drug interactions (DDI).MethodsThis retrospective observational study used administrative pharmacy claims data from the Irish Primary Care Reimbursement Service. Prescriptions dispensed to adults in 2015 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
18
1
2
Order By: Relevance
“…Furthermore, a previous study reported that FDCs were associated with increased risk of therapeutic duplication. 31 In conclusion, this 3-period replicate crossover study demonstrated the BE of the FDC formulation of amlodipine, valsartan, and atorvastatin and the separate formulations of an amlodipine/valsartan tablet and an atorvastatin tablet by using a reference-scaled average BE approach.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, a previous study reported that FDCs were associated with increased risk of therapeutic duplication. 31 In conclusion, this 3-period replicate crossover study demonstrated the BE of the FDC formulation of amlodipine, valsartan, and atorvastatin and the separate formulations of an amlodipine/valsartan tablet and an atorvastatin tablet by using a reference-scaled average BE approach.…”
Section: Discussionmentioning
confidence: 68%
“…Also, it should be noted that it is difficult to delicately adjust the dose of each component in FDCs, although dose titration is quite important in some patients with HTN. Furthermore, a previous study reported that FDCs were associated with increased risk of therapeutic duplication …”
Section: Discussionmentioning
confidence: 99%
“…Лишь недавно в ходе выполнения крупного ретроспективного исследования [28] была предпринята попытка проверить гипотезу о том, увеличивает ли назначение КАГППД риск ошибок при назначении антигипертензивной терапии, в частности, риск необоснованных дублирований в назначении, и риск возможных нежелательных лекарственных взаимодействий по сравнению со СКАГП. В исследование были включены данные о 307833 назначениях КАГППД (67% всех назначений) и данные о 151632 назначениях СКАГП.…”
Section: комбинированная антигипертензивная терапия как необходимое уunclassified
“…In order to answer this question, Moriarty and colleagues1 retrospectively evaluated all primary healthcare prescriptions in Ireland for the 2015 year, using the Primary Care Reimbursement Services administrative pharmacy claims database. The primary outcome was therapeutic duplication, defined as the use of an anti-hypertensive drug of the same class in an FDC preparation and as a separate drug, prescribed at the same time.…”
mentioning
confidence: 99%